Python machine learning : machine learning and deep learning with python, scikit-learn, and tensorflow 2 - Raschka, Sebastian; Mirjalili, Vahid (Packt Publishing, Limited, 2019)
Python Machine Learning, Third Edition is a comprehensive guide to machine learning and deep learning with Python. Packed with clear explanations, visualizations, and working examples, the book covers all the essential machine learning techniques in depth. This new third edition is updated for TensorFlow 2 and the latest additions to ...